As personagens do jornalismo de celebridades: Hart e Bob como representações do jornalismo na animação Os padrinhos mágicos - Maria Aparecida Pinto (2016)
In this study, the objective is to analyze how discourses of celebrity journalism in American cartoon shown in Brazil The Fairly Odd Parents are constructed, in order to understand how the work is represented. This journalism is considered as a specialized part of the Field where social reality is understood through the events that relate about celebrities. We see the historical construction of a professional culture in which they engender languages, actions, perspectives and ways of being that involve identification of celebrity journalism like discourse. This situation approaches this practice of the infotainment's media productions and departs from that noble journalism's sectors, politics and economics. The celebrity journalism is questioned about their social importance and about their journalistic practice condition. Studies about the infotainment allow develop how this distinction between the journalistic specializations is historically constructed, considering the notion of public sphere. The episodes The blondes have more fun and Anti Poof of The Fairly Odd Parents comprise the corpus of research. The French discourse analysis is the theoretical and methodological perspective adopted. The representation of the specialty is analyzed through characters that are celebrity journalists, Hart and Bob Glimmer, based on concepts of socio-discursive imaginary (CHARAUDEAU, 2007) and ethos (MAINGUENEAU, 2012). Hart and Bob lampoon the ethos of celebrity journalism, but mock the ethos of the Field too. The celebrity journalism is historically constructed, being constituted by the political, economic, social and ideological dynamics, but also forming them.